2019
DOI: 10.1093/hropen/hoz002
|View full text |Cite
|
Sign up to set email alerts
|

Live birth rate after intrauterine insemination is not different between women with lower quartile versus higher quartile normal range thyroid stimulating hormone levels

Abstract: STUDY QUESTION Does lower quartile normal range thyroid stimulating hormone (TSH) compared to higher quartile normal range in women without thyroid hormone substitution affect live birth rate after a complete IUI treatment series? SUMMARY ANSWER Lower quartile normal range TSH, in women without thyroid hormone substitution, does not affect live birth rate after a complete intrauterine insemination treatment series compared to higher quartile normal range TSH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(35 reference statements)
0
8
1
Order By: Relevance
“…In addition, the rates of pregnancy, miscarriage, and live births in infertile women with TSH ≥2.5 μIU/mL were similar to those with TSH <2.5 μIU/mL [9,10,13,15]. Although a few studies have reported that infertile women with TSH ≥2.5 μIU/mL have a lower pregnancy rate [16] and lower ovarian reserve [17] than those with TSH <2.5 μIU/mL, the present study was not able to show the difference mentioned before, similar to most previous studies [9,10,13,15].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In addition, the rates of pregnancy, miscarriage, and live births in infertile women with TSH ≥2.5 μIU/mL were similar to those with TSH <2.5 μIU/mL [9,10,13,15]. Although a few studies have reported that infertile women with TSH ≥2.5 μIU/mL have a lower pregnancy rate [16] and lower ovarian reserve [17] than those with TSH <2.5 μIU/mL, the present study was not able to show the difference mentioned before, similar to most previous studies [9,10,13,15].…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have reported the obstetric characteristics and outcomes of infertile women with 2.5 ≤ TSH < 4.5 μIU/mL compared with those with TSH <2.5 μIU/mL [9,10,[13][14][15]. Infertile women with TSH ≥2.5 μIU/mL had similar embryo quality as those with TSH <2.5 μIU/mL [14].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, Karmon et al reported that preconception TSH levels in the high normal range (2.5-4.99 mIU/ml) had no significant effect on clinical pregnancy rates in infertile patients undergoing IUI treatment for various indications, including male factor infertility, diminished ovarian reserve, anovulation and unexplained infertility [15]. Repelaer van Driel-Delprat et al studied the effects of TSH levels in a heterogenous group of euthyroid women who underwent up to a maximum of six cycles of IUI and found no difference in the rate of live birth, clinical and ongoing pregnancy, or pregnancy loss in patients with TSH levels between 2.35 and 4.5 mIU/L compared to women with TSH levels below 2.5 mIU/L [16].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Karmon et al reported that preconception TSH levels in the high normal range (2.5-4.99mIU/ml) had no signi cant effect on clinical pregnancy rates in infertile patients undergoing IUI treatment for various indications, including male factor infertility, diminished ovarian reserve, anovulation and unexplained infertility (15). Repelaer van Driel-Delprat et al studied the effects of TSH levels in a heterogenous group of euthyroid women who underwent up to a maximum of six cycles of IUI and found no difference in the rate of live birth, clinical and ongoing pregnancy, or pregnancy loss in patients with TSH levels between 2.35 and 4.5mIU/L compared to women with TSH levels below 2.5mIU/L (16). Independent from thyroid hormone status, thyroid autoimmunity has been linked with an increased risk of pregnancy loss due to miscarriage or premature delivery (17).…”
Section: Discussionmentioning
confidence: 99%